Pisang sŏnŏn = Emergency declaration [videorecording (DVD)] - Han, Chae-rim; Song, Kang-ho, 1967-; Yi, Pyŏng-hŏn, 1970-; Chŏn, To-yŏn, 1973-; Kim, Nam-gil, 1981- (Well Go USA Entertainment, 2022)
A police detective receives a threatening tip about a terrorist attack against a passenger plane but discovers the suspect has already boarded the flight. When a man on board suddenly dies from an infectious virus, fear and chaos spread quickly amongst passengers and crew. As the pilot declares an emergency, can the detective stop this biological weapon from killing everyone onboard in time to safely land or is this flight ultimately doomed to crash?